Solving a system of Caputo-Hadamard fractional differential equations via Perov’s fixed point theorem - Nouar Aziza Souad; Nisse Khadidja; Beloul Said (Annals of the West University of Timisoara: Mathematics and Computer Science)
In this study, we discuss the existence and the uniqueness of the solution to Caputo-Hadamard Cauchy problems for a system of fractional differential equations, by using Perov’s fixed point theorem. Finally, two examples are provided to illustrate our results.